IMPLEMENTASI PROGRAM E-KTP DALAM RANGKA TERTIB ADMINISTRASI KEPENDUDUKAN DI DESA MANGKOL KABUPATEN BANGKA TENGAH - Sri Yuliana (Fakultas Hukum Universitas IBA Palembang, 2020)
Abstract E-KTP is a National KTP that is regulated in Law No. 24 of 2013 concerning Population Administration, Presidential Regulation No. 26 of 2009 concerning the application of KTP based on the National Population Registration Number, and Presidential Regulation No. 35 of 2010 concerning amendments to Presidential Regulation No. 26 of 2009. With the enactment of Law Number 24 of 2013 concerning Population Administration with the aim of establishing orderly population administration in the National scale and ensuring legal certainty of civil rights of the population, also for the benefit of National development programs, so that updating of population data is required, publishing Population Identification Number (NIK) and e-KTP application. One of the improvements in community service in Mangkol Village is the implementation of the e-KTP program in order to improve the orderly administration of population. Before the national e-KTP program was implemented, the Directorate General of Population and Civil Registration of the Ministry of Home Affairs had used the SIAK (Population Administration Information System) application in Regencies / Cities in Indonesia, but in its implementation it turned out that not all districts / cities implemented it. This is due to data communication network problems that have not been able to go online throughout Indonesia and other problems. Based on data and findings in the field as well as observations made by the research team that the implementation of the e-KTP program in Mangkol Village has not been effective in its implementation due to various factors: 1. The distance where the e-KTP making is far enough causes the slow implementation of the e-KTP program in the Village Bowl. 2. As a result of the Mangkol Village area directly bound by the City of Pangkalpinang. 3. Mangkol Village area which is a division of the City of Pangkalpinang is one of the factors in the slow implementation of the e-KTP program in Mangkol Village Abstract E-KTP is a National KTP that is regulated in Law No. 24 of 2013 concerning Population Administration, Presidential Regulation No. 26 of 2009 concerning the application of KTP based on the National Population Registration Number, and Presidential Regulation No. 35 of 2010 concerning amendments to Presidential Regulation No. 26 of 2009. With the enactment of Law Number 24 of 2013 concerning Population Administration with the aim of establishing orderly population administration in the National scale and ensuring legal certainty of civil rights of the population, also for the benefit of National development programs, so that updating of population data is required, publishing Population Identification Number (NIK) and e-KTP application. One of the improvements in community service in Mangkol Village is the implementation of the e-KTP program in order to improve the orderly administration of population. Before the national e-KTP program was implemented, the Directorate General of Population and Civil Registration of the Ministry of Home Affairs had used the SIAK (Population Administration Information System) application in Regencies / Cities in Indonesia, but in its implementation it turned out that not all districts / cities implemented it. This is due to data communication network problems that have not been able to go online throughout Indonesia and other problems. Based on data and findings in the field as well as observations made by the research team that the implementation of the e-KTP program in Mangkol Village has not been effective in its implementation due to various factors: 1. The distance where the e-KTP making is far enough causes the slow implementation of the e-KTP program in the Village Bowl. 2. As a result of the Mangkol Village area directly bound by the City of Pangkalpinang. 3. Mangkol Village area which is a division of the City of Pangkalpinang is one of the factors in the slow implementation of the e-KTP program in Mangkol Village